IQGAP3, a YAP target, is required for proper cell-cycle progression and genome stability - Leone, Marina; Cazorla-Vazquez, Salvador; Ferrazzi, Fulvia; Wiederstein, Janica L.; Grundl, Marco; Weinstock, Grit; Vergarajauregui, Silvia; Eckstein, Markus; Kruger, Marcus; Gaubatz, Stefan; Engel, Felix (Molecular Cancer Research, 2021)
Controlling cell proliferation is critical for organism development, tissue homeostasis, disease, and regeneration. IQGAP3 has been shown to be required for proper cell proliferation and migration, and is associated to a number of cancers. Moreover, its expression is inversely correlated with the overall survival rate in the majority of cancers. Here, we show that IQGAP3 expression is elevated in cervical cancer and that in these cancers IQGAP3 high expression is correlated with an increased lethality. Furthermore, we demonstrate that IQGAP3 is a target of YAP, a regulator of cell cycle gene expression. IQGAP3 knockdown resulted in an increased percentage of HeLa cells in S phase, delayed progression through mitosis, and caused multipolar spindle formation and consequentially aneuploidy. Protein–protein interaction studies revealed that IQGAP3 interacts with MMS19, which is known in Drosophila to permit, by competitive binding to Xpd, Cdk7 to be fully active as a Cdk-activating kinase (CAK). Notably, IQGAP3 knockdown caused decreased MMS19 protein levels and XPD knockdown partially rescued the reduced proliferation rate upon IQGAP3 knockdown. This suggests that IQGAP3 modulates the cell cycle via the MMS19/XPD/CAK axis. Thus, in addition to governing proliferation and migration, IQGAP3 is a critical regulator of mitotic progression and genome stability. Implications: Our data indicate that, while IQGAP3 inhibition might be initially effective in decreasing cancer cell proliferation, this approach harbors the risk to promote aneuploidy and, therefore, the formation of more aggressive cancers.
CRIS-Team Scopus Importer:2021-11-05